2016
DOI: 10.1016/j.jgr.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rd alleviates mouse acute renal ischemia/reperfusion injury by modulating macrophage phenotype

Abstract: BackgroundGinsenoside Rd (GSRd), a main component of the root of Panax ginseng, exhibits anti-inflammation functions and decreases infarct size in many injuries and ischemia diseases such as focal cerebral ischemia. M1 Macrophages are regarded as one of the key inflammatory cells having functions for disease progression.MethodsTo investigate the effect of GSRd on renal ischemia/reperfusion injury (IRI) and macrophage functional status, and their regulatory role on mouse polarized macrophages in vitro, GSRd (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Ginsenosides such as Rd and Rb1 have been reported to affect macrophage polarization and atherosclerosis progression; however, there has been no related research on diabetic atherosclerosis ( Ren et al, 2016 ; Zhang et al, 2017 ). This report revealed that 20(S)-Rg3 could reduce the plaque burden and enhance plaque stability in diabetic mice, the effects of which were mostly achieved by suppressing AGEs-induced M1 macrophage activation and promoting M2 macrophage polarization via PPARγ activation ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenosides such as Rd and Rb1 have been reported to affect macrophage polarization and atherosclerosis progression; however, there has been no related research on diabetic atherosclerosis ( Ren et al, 2016 ; Zhang et al, 2017 ). This report revealed that 20(S)-Rg3 could reduce the plaque burden and enhance plaque stability in diabetic mice, the effects of which were mostly achieved by suppressing AGEs-induced M1 macrophage activation and promoting M2 macrophage polarization via PPARγ activation ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cells, such as macrophages and neutrophils, let leukocytes and plasma components come to sites where infection or injury has occurred during inflammation to eliminate dangers (Nowarski et al 2013;Lee et al 2016). Although inflammation is important to the immune system, excessive activity of inflammatory cells can cause cancer, rheumatoid arthritis, multiple sclerosis, chronic asthma, psoriasis, and other diseases (Gautam and Jachak 2009;Nowarski et al 2013;Ren et al 2016). To treat those inflammation-driven diseases, inflammatory responses should be controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory cells, such as macrophages and neutrophils, let leukocytes and plasma components come to sites where infection or injury has occurred during inflammation to eliminate dangers [ 1 , 2 ]. Although inflammation is important to the immune system, excessive activity of inflammatory cells can cause cancer, rheumatoid arthritis, multiple sclerosis, chronic asthma, psoriasis, and other diseases [ 1 , 3 , 4 ]. To treat those inflammation-driven diseases, inflammatory responses should be controlled.…”
Section: Introductionmentioning
confidence: 99%